Mixed ionic-electronic conductivity, phase stability and electrochemical activity of Gd-substituted La2NiO4+δ as oxygen electrode material for solid oxide fuel/electrolysis cells - Pikalova, Elena (2021)
Ruddlesden-Popper La2-xGdxNiO4+δ (x = 0-0.4) nickelates were synthesized by glycerol-nitrate combustion technique and explored as potential oxygen electrode materials for solid oxide fuel/electrolysis cells. Similar to the parent La2NiO4+δ, the metastability of RP-type n = 1 structure limits the applicability of La2-xGdxNiO4+δ to temperatures below 900°C. These solid solutions are mixed conductors with predominantly p-type electronic conductivity that exceeds 50 S/cm at 500-800°C in air. Substitution by gadolinium does not change the overstoichiometric oxygen content in air but has a negative impact on the mobility of interstitial oxygen, most likely, due to steric effects associated with the lattice shrinkage on doping. The electrochemical activity of bilayer electrodes comprising functional La2-xGdxNiO4+δ and current collecting LaNi0.6Fe0.4O3-δ + 3wt.% CuO layers in contact with Ce0.8Gd0.2O1.9 electrolyte was studied in air at 550-850°C. Analysis of electrochemical impedance spectroscopy data employing the ALS (Adler-Lane-Steele) model revealed the limiting role of oxygen-ionic conductivity of functional La2-xGdxNiO4+δ materials in overall electrode performance.